Acceptance and use of virtual reality and its impact towards learning attitude among young adults in Shah Alam, Selangor, Malaysia - Abdul Rahman, Aris; Murad, Khairudin; Adnan, Wardatul Hayat (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Virtual Reality (VR) technology is a computer simulation system that creates new learning experiences in the virtual world. VR creates a simulation environment that has an impact on learning attitude and this new environment interacts with three-dimensional dynamic views that has an impact physical learning behaviour. Virtual reality is part of an innovation process where the user interacts with real-time simulation and the remarkable t advanced technology tools to understand better, on the products. The traditional learning method is monotonous, and the current study is an interactive learning process that saved time, enhanced young people' learning attitudes and gave them the ability to learn anywhere at any time. The study aims to identify virtual reality acceptance and use among young adults and its impact towards learning attitude. Learning attitudes that are measured within this study are excitement and happy feelings when using VR. One of the impactful growths of VR is the use of virtual technology in education institutions where universities and schools are emphasising alternative ways of learning. This confirms the researcher’s thoughts that acceptance and use of VR is essential in today’s world which focusses on digitalisation technology. A quantitative methodology was applied in this study, where face to face surveys through the distribution of questionnaires was given out to a group of 200 young adults from the Shah Alam community in Selangor, Malaysia. The study shows that Virtual Reality Hedonic Motivation is the highest factor influencing Virtual Learning Behavioural Intention that leads towards acceptance and use (Pearson correlation r=.741 and Regression R2 = .549). Thus, the findings and discussion will be further added to the present literary works and helps future researchers improve learning attitudes towards young adults with the adaptation of VR, specifically in a Malaysian context.